For a Partnership between International Transitions Review and ASAP Observatory for the Study of Social and Societal Transitions - Meier, Olivier (International Transitions, 2024)
ASAP Observatory and the journal «International Transitions» share common goals through the study of social and societal changes that influence and are influenced by different cultural contexts and international transitions. I am enthusiastic about developing interdisciplinary research projects that intersect the fields of sociology, economics, management sciences, political science, and intercultural studies. Pooling our scientific networks will allow us to deepen themes such as the management of cultural diversity in public policies, the impact of ecological transition policies on different cultural communities, and the dynamics of social change in a globalized world. Undoubtedly, the partnership between our two institutions will help bring new perspectives on emerging societal challenges in a rapidly and profoundly changing world.